Agroecology and household production diversity and dietary diversity: Evidence from a five-year agroecological intervention in rural Malawi. (November 2021) - Kansanga, Moses Mosonsieyiri; Kangmennaang, Joseph; Bezner Kerr, Rachel; Lupafya, Esther; Dakishoni, Laifolo; Luginaah, Isaac
Abstract: Following a decade of declining food insecurity, the global undernourished population has increased successively in the last three years. This increasing trend highlights the challenge of meeting the zero hunger and nutrition targets of Sustainable Development Goal (SDG) 2. Malawi is one of the most food insecure countries in Africa, with a significant proportion of its population being undernourished. Amid evidence of the counter-productive effects of input-intensive agriculture in this context, including the narrowing of the food basket and unequal access to subsidized inputs, some scholars have argued that alternative diversified agricultural approaches, combined with attention to underlying inequalities, maybe more promising in addressing undernutrition. Agroecology is one such approach which promotes biodiversity and pays attention to socio-political inequalities. That notwithstanding, there is limited research on the potential role of agroecology in improving household food outcomes. Drawing theoretical insights from political ecology and using Difference-in-Difference and mediation techniques, we examine the impact of agroecology on household production diversity and dietary diversity using data from a five-year agroecological intervention in Malawi (n = 514 agroecology-practicing farming households and 400 non-agroecology households). Findings from the Difference-in-Difference analysis show a positive treatment effect of agroecology on both production diversity (β = 0.289, p < 0.01) and dietary diversity (β = 0.390, p < 0.01). Results from the mediation analysis indicate that generally, production diversity is directly associated with dietary diversity (β = 0.18, p < 0.01), although the relationship is stronger for households practicing agroecology (β = 0.19, p < 0.01) compared to non-agroecology households (β = 0.14, p < 0.01). These findings provide evidence of the potential for agroecology to improve nutrition in smallholder farming contexts and contribute to achieving SDGs 2. Malawi is currently grappling with widespread micronutrient deficiencies. Given that smallholder farmers typically draw a significant proportion of their diet from what they produce, farming approaches like agroecology, which emphasizes the cultivation of diverse crops, may be promising for improving household nutrition. Highlights: Undernutrition is of major concern in Malawi. We examine the impact of agroecology on production diversity and dietary diversity. Agroecology can improve production diversity and dietary diversity. Agroecology has the potential to contribute to achieving SDG 2.